The Impact of Cargo Volume and Ship Type on Maritime Service Efficiency: A Case Study of Indonesia - Achmad Bashori; Ni Kadek Selvi Pricilia; Laila Puspitasari Anggraini; Siwi Woro Herningsih; Ahmad Munawir; Ahmad Shulhany (Journal Marine Inside, 2025)
Port service efficiency plays a crucial role in supporting maritime logistics and national trade performance. One key indicator of port service efficiency is ship turnaround time, which is influenced by various operational factors, including ship type and cargo volume. This study examines the effect of ship type and cargo volume on ship turnaround time at Tanjung Priok Port, Indonesia, using a case study of PT Buana Lintas Lautan Tbk. Quantitative analysis was conducted using monthly operational data collected over a twelve-month period (August 2022–August 2023). Multiple linear regression was applied after fulfilling classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results indicate that ship type and cargo volume simultaneously have a significant effect on turnaround time. However, partial analysis reveals that only cargo volume has a significant positive impact on turnaround time, while ship type does not show a statistically significant effect. These findings suggest that operational delays are primarily driven by cargo handling intensity rather than vessel characteristics. This study provides practical insights for ship agency companies and port operators in estimating service time, optimizing operational planning, and improving port service efficiency through better cargo management strategies. Efisiensi pelayanan pelabuhan merupakan faktor penting dalam mendukung kelancaran logistik maritim dan kinerja perdagangan nasional. Salah satu indikator utama efisiensi pelayanan pelabuhan adalah ship turnaround time, yang dipengaruhi oleh berbagai faktor operasional, termasuk jenis kapal dan volume muatan. Penelitian ini bertujuan untuk menganalisis pengaruh jenis kapal dan volume muatan terhadap ship turnaround time di Pelabuhan Tanjung Priok, Indonesia, dengan studi kasus pada PT Buana Lintas Lautan Tbk. Penelitian ini menggunakan pendekatan kuantitatif dengan data operasional bulanan selama periode Agustus 2022 hingga Agustus 2023. Analisis data dilakukan menggunakan regresi linear berganda yang didahului dengan pengujian asumsi klasik, meliputi uji normalitas, multikolinearitas, heteroskedastisitas, dan autokorelasi. Hasil penelitian menunjukkan bahwa jenis kapal dan volume muatan secara simultan berpengaruh signifikan terhadap ship turnaround time. Namun, secara parsial hanya volume muatan yang berpengaruh positif dan signifikan terhadap ship turnaround time, sedangkan jenis kapal tidak menunjukkan pengaruh yang signifikan. Temuan ini mengindikasikan bahwa lamanya waktu pelayanan kapal lebih dipengaruhi oleh intensitas penanganan muatan dibandingkan karakteristik jenis kapal. Hasil penelitian ini diharapkan dapat menjadi acuan bagi perusahaan keagenan kapal dan pengelola pelabuhan dalam memperkirakan waktu pelayanan kapal, meningkatkan perencanaan operasional, serta mengoptimalkan efisiensi pelayanan pelabuhan.